The Florida Bull Test 2016–2017 - Luara B. Canal; Graham Cliff Lamb; Nicolas DiLorenzo (EDIS)
The 17th annual Florida Bull Test Sale was held on January 21, 2017 at the conclusion of the 2016-2017 Florida Bull Test. The test evaluated the performance potential and breeding soundness of bulls consigned to the program at the UF/IFAS North Florida Research and Education Center (NFREC). This new 9-page fact sheet discusses test procedures, assessment of feed efficiency, test rules and regulations, health requirements, and test results. Written by Luara B. Canal, G. Cliff Lamb, and Nicolas DiLorenzo, and published by the UF/IFAS Department of Animal Sciences, February 2018. http://edis.ifas.ufl.edu/an341